A Robust Sub-Threshold, Low Power-Delay, Energy and Area Efficient Level Shifter - Fassio, Luigii (Institute of Electrical and Electronics Engineers, 2021)
IEEE TRANSACTIONS ON CIRCUITS AND SYSTEMS II-EXPRESS BRIEFS